Predictive factors of quality of life among older adults in rural Indonesia: a cross-sectional study - Pagela Pascarella Renta; Rahmad Rahmad (Intelektual Pustaka Media Utama, 2026)
The older adults are a vulnerable group facing physical, social, and economic health challenges that impact their quality of life. Information on the quality of life of the older adults in rural Indonesia is still limited, so this study aims to identify predictors of quality of life in the older adults in the working area of the Dusun Tengah Community Health Center, Lubuk Sandi District, Seluma Regency, Bengkulu Province, Indonesia. This quantitative cross-sectional study involved 60 elderly individuals who met the inclusion criteria. The research instruments included quality of life with WHOQOL-BREF, activities of daily living with the Barthel Index, ambulation with CAS, mobility with the timed up and go (TUG) Test, and lower limb muscle strength with the 30-second STS Test. The results showed that age, employment status, income, walking ability, mobility, lower limb muscle strength, and activities of daily living were significantly associated with quality of life (p < 0.05). In contrast, gender, education level, and social support were not significantly associated with quality of life. Multivariate analysis identified walking ability (OR = 13.65; 95% CI: 1.03-180.61) and income (OR = 5.81; 95% CI: 1.02-33.07) as the most dominant predictors of quality of life in the older adults. These findings provide important implications that interventions to improve the quality of life in older adults in primary health care need to prioritize programs to improve ambulation, prevent physical function decline, and strengthen the economic aspects of older adults, especially in rural areas.